An analysis of literature on sport officiating research - Hancock, D. J.; Bennett, S.; Roaten, H.; Chapman, K.; Stanley, C. (Research Quarterly for Exercise and Sport, 2021)
Sport officials are crucial members of sport. Researchers have studied their roles numerous times, with results often informing sport procedures (e.g., athlete order in artistic sports). As the research on sport officiating spans five decades and several topics of interest, it is important that researchers periodically synthesize the literature. Purpose: The purpose of this study, therefore, was to conduct an analysis of literature on sport officiating research.